Pembinaan Kegiatan Mahasiswa Lintas Perguruan Tinggi Mensukseskan Bina Sekolah - Ashari Ismail; Firman Umar; Idham Irwansyah; Mauliadi Ramli; Jusnawati Jusnawati (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
This dedication is part of an effort to encourage students to carry out school development. School development activities are activities related to the dharma of community service, which shows how concerned higher education institutions are, in providing educational services to the surrounding community, including elementary school level institutions. This guidance was given to students who were assigned to carry out school development at Lekoboddong Elementary School, Tompobulu, Maros Regency, South Sulawesi. By using informal and formal assistance guidance techniques, the guidance process is carried out through the following stages: coordinating students with the Maros National Education Office and the Lekoboddong Elementary School Principal, and providing materials/preparation to school development actors. The results of the guidance show that students' understanding of the urgency of school development and the need to maintain effective relationships with school-building group partners